Materiales didácticos y su incidencia en el aprendizaje de los niños de Educación Inicial II - Suárez Verdezoto, Magdalena (2024)
The present investigation focused on determining the impact of teaching materials on learning in children of Initial Education II, of the “Gabriel García Moreno” Educational Unit, of the Ricaurte parish, Urdaneta Canton, Los Ríos Province. Through an applied diagnosis, it was detected that in sublevel 2 there is a shortage of teaching materials, which directly affects the children who attend this sublevel in whom demotivation, lack of concentration, and commitment to activities were noted, which together affects their learning process. learning. The research was qualitative and used a non-experimental, documentary and field design. The study population was made up of teachers and children from Sublevel II, the selection of the sample was carried out intentionally, delimiting Sublevel II “A” for this study. The data collection techniques were interviewing teachers and observing children, complemented by instruments such as the questionnaire and observation sheet. Based on the objectives set, the results allowed us to obtain information about the variety of teaching materials available in the educational unit, as well as their use and the impact on the development of specific skills of the child; and teachers' perception of the effectiveness of teaching materials in learning. The research provided an identification of the level of availability and accessibility of teaching materials in the educational environment in order to identify possible areas of improvement.